Perancangan Website Iklan Radio Kota Salatiga menggunakan Framework Laravel - Leo Candra Gunawan Wicaksono; Eko Sediyono (Jurnal Informatika, 2023)
Technology has entered any field and has an important role to make every work process faster and more efficient. Thus, the admin application web system and radio advertisement recording are needed to assist in the process of recording, printing and depositing radio advertisements. This research application web system will be created using the Laravel framework and the PHP programming language. Laravel is a php-based web application framework that uses easy-to-understand models, views and controllers. The prototype method is a method that will provide an initial picture or concept as an experimental design that can make it easier for researchers to find out how the system can run well.